Development of indicators for a nationwide cross-sectoral quality assurance procedure for mental health care of patients with schizophrenia, schizotypal and delusional disorders in Germany = Entwicklung von Indikatoren für ein bundesweites, sektorenübergreifendes Qualitätssicherungsverfahren zur Versorgung von Patienten mit Schizophrenie, schizotypen und wahnhaften Störungen in Deutschland - Stegbauer, Constance; Szecsenyi, Joachim (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen, 2017)
Purpose: This paper describes the development of quality indicators for an external statutory and cross-sectoral quality assurance (QA) procedure in the context of the German health care system for adult patients suffering from schizophrenia, schizotypal and delusional disorders (F20-F29). Methods: Indicators were developed by a modified RAND/UCLA Appropriateness Method with 1) the compilation of an indicator register based on a systematic literature search and analyses of health care claims data, 2) the selection of indicators by an expert panel that rated them for relevance and for feasibility regarding implementation. Indicators rated positive for both relevance and feasibility formed the final indicator set. Results: 847 indicators were identified by different searches. Out of these, 56 were selected for the indicator register. During the formal consensus process the expert panel recommended another 45 indicators so that a total of 101 indicators needed to be considered by the panel. Of these, 27 indicators rated both relevant and feasible were included in the final set of indicators: this set included 4 indicators addressing structures, 19 indicators addressing processes and 4 indicators addressing outcomes. 17 indicators of the set will be reported by hospitals and 8 by psychiatric outpatient facilities. Two indicators considered to be cross-sectoral will be reported by both sectors. Discussion: F20-F29 and its treatment show some specific features which so far have not been addressed by any procedure within the statutory QA program of the German health care system. These features include: Schizophrenia and related disorders a) are potentially chronic conditions, b) are mainly treated in outpatient settings, c) require a multi-professional treatment approach and d) are treated regionally in catchment areas. These specific features in combination with the peculiarities of some legal, political and organizational characteristics of the German health care system and its statutory QA program have strongly influenced the development of indicators. The result was a seemingly “imbalanced” set of indicators with a greater number of indicators for inpatient than for outpatient care despite the fact that clinical reality is otherwise. Conclusions: The circumstances of the German health care system that restricted the development of this cross-sectoral QA procedure addressing care for F20-F29 are also most likely to emerge with the development of cross-sectoral QA procedures for other (potentially) chronic conditions that are mainly treated in the outpatient setting by multi-professional teams or by networks of different providers. In order to be able to develop a QA procedure that mirrors the reality of service provision for (potentially) chronic diseases such as F20-F29 we need to explore further current and new data sources, diminish sectoral borders, and implement health care responsibility on the level of catchment areas.